Some physical parameters influencing the comprehensive evaluation of kinetic data in photochemical reactions and its application in the periodate-chemistry - Valkai, László; Marton, Antal; Horváth, Attila K. (Journal of photochemistry and photobiology. A, Chemistry., 2020)
[Display omitted] •Comparing the emitted light of lamps by an external detector and some corrections.•Emission spectra measured by diode-array instruments itself cannot be directly used.•Determination of the actual irradiation time may be a complex problem in some cases.•Photochemical decomposition of orthoperiodate.•Photochemical decomposition of periodate does not affect the measured absorbance. Quantitative treatment of photochemical processes requires precise knowledge of the amount of photons reaching the sample. A possible and probably the most convenient way is to investigate a photochemical reaction subject to be studied by conventional or diode-array spectrophotometers. The self-test mode of the given instrument usually provides an opportunity for any user to obtain the measurable components of the emission spectrum of the lamp. This spectrum may then be used to determine the rate of primary photochemical processes as recently proposed by Fábián and Lente, alongside with molar absorbance, concentration of the absorbing species, quantum yield, and the absorbance measured itself. However, in some cases, the spectrum obtained by this way has to be treated with special circumspection because the amount of light may significantly differ from each other in the sample compartment and in other parts of the instrument as well. The most important technical factors influencing the emission spectrum of the light are discussed and their suitable utilization may straightforwardly provide a comparable amount of photons reaching the sample. To present it, different light sources of several spectrophotometers were systematically surveyed and some feasible corrections were as well highlighted. The considerations illustrated here are applied and demonstrated in case of sodium periodate providing a solid basis for a sound quantitative description of its photochemical decomposition.